MANAJEMEN PESERTA DIDIK DALAM MEWUJUDKAN KARAKTER BUDAYA LOKAL - Muhammad Nasih; Dewi Hilalatul Hamid Agtin (Institut Agama Islam Darussalam Blokagung, 2023)
The purpose of this study was to describe the management of students in realizing the local cultural character of students at sd negeri 9 Barurejo Banyuwangi as well as the supporting and inhibiting factors. The type of research used is descriptive qualitative. The informants of this research include; principals, teachers, and students. Data collection methods used are observation, interviews, and documentation. The technique chosen in data analysis is data collection, data condensation, data presentation, and drawing conclusions. And the results of this study indicate that the management of students at SD Negeri 9 Barurejo has been going well as evidenced by the fact that there are schools that are trying to achieve goals, one of which is by channeling and developing general abilities or intelligence, talents and interests of students so that through the existence of cultural character local. The local cultural characters in question are religious culture, discipline culture, responsibility culture, and artistic culture in this case the art culture of gendering dance, hadrah, scouts, and drum bands, all of which are local cultures that can shape the character of the students at the school. The supporting factors are support from the principal, teacher motivation, student enthusiasm, adequate infrastructure, and enthusiasm from the guardian. while the inhibiting factor is a matter of time management, environment, and interests of students.